A facile and expeditious approach to substituted 1H-pyrazoles catalyzed by iodine. Issue 24 (15th June 2016) - Zhang, Hailei; Wei, Qian; Zhu, Guodong; Qu, Jingping; Wang, Baomin
Graphical abstract: Highlights: A facile and expeditious approach to 1 H -pyrazoles is developed. Starting materials are α, β-unsaturated ketones/aldehydes and sulfonyl hydrazide. The reaction is catalyzed by as low as 2 mol % I2 . The process features simple conditions, high yield, and broad substrate scope. Abstract: A facile and expeditious method for the synthesis of 1 H -pyrazoles by the reaction of α, β-unsaturated aldehydes/ketones and sulfonyl hydrazide catalyzed by as low as 2 mol % I2 has been demonstrated. This synthetic system features simple operation and mild reaction conditions, and displays a broad functional group tolerance furnishing good to excellent yields.